İKİNCİ SOFİSTİK DÖNEM: SOFİST, RETOR VE FİLOZOFLARIN DİNİ GÖREVLERİ. - KAYA, ELİF AKGÜN (CEDRUS, 2017)
Literary sources, epigraphical documents, and numismatic evidence show that the sophists, rhetors, and philosophers that belonged to the most prominent and the wealthiest families had an excellent education and so they officiated successfully many public services and generously spent their money for the cities in the Second Sophistic Period (Ist to IIIrd centuries AD). They undertook important municipal magistracies such as βούλαρχος, βουλευτής, γραμματεύς, στρατηγός, ἀρχιερεύς, δᾳδοῦχος, ἱερεύς, ἱεροφάντης, νεωκόρος, νεοποιός, περιθύτης, προφήτης, ἀγορανό- μος, λογιστής ve ταμίας, γυμνασίαρχος, ἐφήβαρχος, ἀγωνοθέτης, εἰρήναρχος/εἰρηνάρχης, στεφανήφορος, πρύτανις/πρυτανάρχης. Also, it is documented that they took on quite prestigious provincial magistracies such as ἀγωνοθέτης, ἀρχιερεύς/ἀσιάρχης, and γαλα- τάρχης. In this article, religious services of sophists, rhetors, and philosophers in the Second Sophistic Period are investigated. Philostratos (VS) and epigraphical documents assert that these persons took on important religious duties such as arkhiereus, hiereus, dadoukhos, hierophantes, neokoros, neopoios, perithytes and prophetes. They fulfilled these tasks in their own cities as well as in other cities they became citizens. It is obvious that rhetors were more active in public tasks; but, the number of sophists who took on religious duty was more than the rhetors. On the other hand, it is determined that philosophers generally fell behind sophists and rhetors about undertaking public duties and obtaining privileges.